Aerospace series. Connector, electrical and optical, rectangular, modular, rectangular inserts, operating temperature 175 °C (or 125 °C) continuous. Receptacle, size 2, with flange, class A, C and E. Product standard Part 025, (30th November 2015) - British Standards Institution,
No abstract available